Effect of early physiotherapy on neuroglial interaction after injury to the motor cortex - Rodrigues, R. W. P.; Berber, G. C. M.; Berber, R. C. A. (Scientific Electronic Archives, 2018)
The term cerebral plasticity covers the possible mechanisms of neuronal reorganization, recruitment of functionally homologous pathways, synaptogenesis, dendritic arborization and activation of secondary areas. Cerebral reorganization still begins in the acute phase after the cortical lesion, with progressive improvement until the stabilization of the condition. Although cortical remodeling is most noticeable during the early stages, changes in brain activity continue until one year after injury. The processes of repair and reorganization of the central nervous system that begin soon after the injury, added to the physiotherapy rehabilitation intensified in the initial phase, will favor the learning or relearning the motor of the patient after the neuronal injury, because the rehabilitation process will happen at the peak of plasticity, thus favoring their motor responses. Several techniques have been used for the recovery of motor function, however there are controversies as to the result in neuroplasticity. The relationship between synaptic efficiency and microglial activation is still not well described in the literature. It is believed that during a specific task, the phagocytic activity of the microglia causes weaker synapses to be eliminated, leading to a greater activation of stronger synapses, thus, early physiotherapy in the early phase may promote the repair and healing process in the damaged areas, as well as, may favor the trophism and plasticity of the remaining neurons. Thus, this work aimed to review on neuro-glial interaction and neuronal plasticity, related to the aspects of early physiotherapy.